APPLICATION OF THE RASCH METHOD OF EVALUATING LATENT VARIABLES IN MANAGEMENT AND ADMINISTRATION - Maslak, Anatoly; Moiseev, Sergey; Nasonova, Tatiana (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2018)
In the paper approaches of application of the theory of latent variables for the decision of some problems of management and management are offered. The peculiarity of this work is that mathematical solutions for solving problems are based on Rasch’s model for estimating latent variables.The aim of this paper is to describe a general approach to estimating latent variables using Rasch’s method, based on the method of least squares, and apply this approach to some management tasks. The tasks of applying the Rasch model to the method of organizing team, to evaluating alternatives in decision-making and to the formation of a portfolio of securities were solved.In the field of labour management, three models for organizing group tasks are considered: the formation of work teams, the case of individual performance of a group task, and the case of joint performance of group task jobs. In the field of decision theory, the model for choosing the best alternative is considered, including taking into account the weights of the criteria. We also considered the approach of obtaining estimates of alternatives using the hierarchy analysis method, in which the attractiveness vector of alternatives is computed on the basis of Rasch’s model of estimation of latent variables. In the field of financial management, a method of forming a portfolio of securities in the approach of the theory of latent variables is proposed. It is shown that, in comparison with traditional methods, the approach based on Rasch’s model has advantages: linearity of the obtained estimates, their independence and high accuracy.